INCLUSIVE CLASSROOMS STRATEGIES FOR LANGUAGE LEARNING - Bakhronova Nilufar Abdurazzok kizi; Jalolova Shahnoza Muhammadjanovna (TADQIQOTLAR.UZ, 2024)
Abstract: Language learning in inclusive classrooms is a key aspect of inclusive education aimed at creating a supportive and equitable learning environment for students with different learning needs. Inclusive classrooms bring together students of diverse abilities, backgrounds, and linguistic skills, foster a sense of community, and promote academic and social growth. Language learning plays an important role in facilitating communication, cognitive development, cultural understanding and social inclusion among students in diverse classroom settings. Although there are many advantages associated with language learning in inclusive classrooms, there are also limitations and challenges that teachers and students may face. This article explores the potential benefits and limitations of language learning in inclusive classrooms and highlights the importance of promoting language diversity and inclusion in education.